2016
DOI: 10.1155/2016/4804271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aminosilane Modification on Nanocrystalline Cellulose Properties

Abstract: The application of renewable nanomaterials, like nanocrystalline cellulose (NCC), has recently been widely studied by many researchers. NCC has many benefits such as high aspect ratio, biodegradability, and high number of hydroxyl groups which offer great opportunities for modification. In this study, the NCC derived from empty fruit bunches (EFB) was modified with aminosilane, 3-(2-aminoethylamino)propyl-dimethoxymethylsilane (AEAPDMS), and the characterization was performed to investigate the potential as ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…The samples with the highest thermal stability enhancement though were those whose surfaces were completely coated with the siloxane polymer and could enhance the char formation beyond the lower theoretical threshold (i.e., 10Me‐CNF and 10A‐CNF). Our observed thermal stability improvements are in good agreement with other studies in the literature …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The samples with the highest thermal stability enhancement though were those whose surfaces were completely coated with the siloxane polymer and could enhance the char formation beyond the lower theoretical threshold (i.e., 10Me‐CNF and 10A‐CNF). Our observed thermal stability improvements are in good agreement with other studies in the literature …”
Section: Resultssupporting
confidence: 93%
“…Some of these studies have also shown that silane modifications can improve biopolymer thermal stability. For example, Mohd et al improved the thermal stability of nanocrystalline cellulose up to ≈10–25 °C through silanization with 3‐(2‐aminoethylamino)propyl‐dimethoxymethylsilane, at comparable loadings to those used in our study . Similarly, Wang et al enhanced the thermal stability and miscibility of sisal fibres (for poly(lactic acid) composites) by functionalizing them with aminopropyl triethoxysilane, showing TG data but not quantifying the degree of improvement .…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…40,43 The surface modification of (nano)cellulose-based materials by selected OS was also successful for the production of stable emulsions 44,45 and functional films and foams with e.g. high hydrophobicity, 46 enhanced CO 2 47 and oil adsorption capacity, 4 improved thermal stability 48 and antibacterial properties. 49 Most of the surface modifications of CNFs by an OS are commonly performed as a pre-step before material elaboration (usually in organic solvent 50 ), or as a post-modification of the CNFbased product.…”
Section: Introductionmentioning
confidence: 99%